Para onde vais?: as metamorfoses da migração laboral: do homem primitivo ao sujeito de direitos. - Chaves, Tâmara Marília Rodrigues (2018)
What makes the migrant a migrant worker? The first object of this work is to understand, with the resources of the methodologies of historical and bibliographical research, the trajectory that made the primitive migrant a labor migrant and, more than that, a subject of rights not only of his country of origin, but also Internationally. Nevertheless, although with important social and legal advances in the international scope, the migratory labor issue is susceptible to situations of setbacks in the different countries, in the name of state sovereignty. This is the case of Brazil, which is only recently approving its own immigration law capable of repealing the Alien Statute (Law 8615/1980). The aforementioned Statute brings remnants of the military period, maintaining national security and protecting the national worker against the universal interests of human rights enforcement, which should reach national and foreign workers alike. In addition to Conventions Nos. 97, 143 and their Recommendations, the ILO formulated a framework of principles and guidelines (Multilateral Framework for Labor Migration - MMML), with a focus on consolidating migrant labor rights, to be applied by the member countries of this organization in the formulation of their national public policies for labor migrations. Although not binding, one of the principles of the MMML suggests the creation of a database that takes into account the needs of the labor market and the demographic trends of the recipient country, the sending country and the available labor force for migrate. In advance, the risk is that, with the application of this principle, the migrant worker will once again be considered, just as at the height of economic liberalism, as a simple economic category available to the consumer market. On the other hand, the idea of moving migrant workers to the remaining jobs seems promising, mainly because it would reduce the exposure of migrants to the inhumane conditions of moving and do not, as intended, find means of subsistence to work at the chosen place, on a temporary basis or not, while avoiding situations of illegality. In order to assess the effectiveness of this principle, we opted for a practical case recently experienced in Brazil: The Mais Médicos Program, since it was based on demographic trends studies and the needs of the local labor market to accommodate foreign doctors in the country, and on which we ask the following question: the labor migration conducted by Mais Médicos Program, even though the migrant figure as a subject of rights (or, without a proper national law of reception, the risk of reducing migrants to the mere condition of available economic category)? In the end, we conclude that labor migration policies without the lawn of national law consolidated in defense of the migrant worker are not capable of sustaining the humanitarian commitment that each State must assure to the said migrant as a subject of rights.